Ethno-medicinal Plants Used in the Treatment of Diarrhoea & Dysentery by Bhil Tribe of Ratlam District (M.P.) - Jadhav, Dinesh (Indian Forester, 2007)
The paper provides information on the use of plant crude drugs for the treatment of diarrhoea and dysentery by the Bhil tribe of Ratlam District (M.P.). It deals with 25 plant species under 23 genera belonging to 20 families for the treatment of these afflictions. The Bhils of the area depend totally on herbal drugs for their primary health care which is attributed partly to their socio-economic and cultural conditions.